2012
DOI: 10.1111/j.1468-2427.2012.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathways out of Homelessness in Los Angeles and Tokyo: Multilevel Contexts of Limited Mobility amid Advanced Urban Marginality

Abstract: The widespread entrenchment of gaping urban inequality has aroused concern about how economic, demographic and (neoliberal) ideological globalization interacts with local conditions to shape its magnitude, manifestations and experiences. This article explores how the process of exiting homelessness is affected by an interaction of social contexts operating at multiple levels, from the global to the individual. I advance and assess a multilevel framework of exiting homelessness by combining comparison of second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
(110 reference statements)
1
18
0
Order By: Relevance
“…This is consistent with previous research that emphasizes the importance of structural factors for a range of public health concerns (Des Jarlais, 2000, Heimer et al, 2002, Blankenship et al, 2000). The results from this study also converge with previous research on exiting homelessness, which found that recently homeless individuals were able to consistently exit homelessness if they were connected with minimum wage employment and at least one stably housed friend or family member (Marr, 2012). …”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with previous research that emphasizes the importance of structural factors for a range of public health concerns (Des Jarlais, 2000, Heimer et al, 2002, Blankenship et al, 2000). The results from this study also converge with previous research on exiting homelessness, which found that recently homeless individuals were able to consistently exit homelessness if they were connected with minimum wage employment and at least one stably housed friend or family member (Marr, 2012). …”
Section: Discussionsupporting
confidence: 88%
“…Understanding resettlement as a process has led writers to make prominent use of 'pathways' imagery in debates about the explanation of homelessness and resettlement. (See for instance Anderson and Tulloch, 2000;Clapham, 2003;McNaughton, 2008;Ravenhill, 2008;Fopp, 2009;Mallett et al, 2010;Maycock et al, 2011;Marr, 2012;Somerville, 2013;Fitzpatrick et al, 2013;De Decker and Segers, 2014;Raitakari, 2019a). In debates about homelessness, a pathway has been defined as 'the route of an individual or household into homelessness, their experience of homelessness and their route out of homelessness to secure housing' (Anderson and Tulloch, 2000).…”
Section: Resettlement and Pathways Out Of Homelessnessmentioning
confidence: 99%
“…Subjects such as homelessness among day labourers (Aoki 2003;Gill 2001b;Herbert 2004), the sudden increase of homeless people in the 1990s (Ezawa 2002;Kennett and Iwata 2003;Hasegawa 2005), movements for the rights of homeless people (Klinger 2000;Hasegawa 2006) and also countermeasures (Gill 2005;Marr 2012;Obinger 2009;Mizuuchi 2003) were examined. Research about the social networks of homeless people is rare: the work of Shinichiro Iwata and Karato Koji (2011), who conducted research on the impact of social networks on the geographical concentration of homeless people in Ōsaka city, and of Matthew D. Marr (2012), who did research on different strategies of exiting homelessness in Tōkyō and Miami, represents exceptions. Inazuki Tadashi , who published in Japanese, also deals with social networks of homeless people (2006) and the impact of self-sufficiency support on them (2008).…”
Section: Introductionmentioning
confidence: 99%